Relatório de Estágio Profissional - 29 letras, 5 palavras, 1 sonho - Ser professora de Educação Física - Ana Cláudia Miranda Baptista (2018)
Once the professional Internship is over, it is necessary to reflect on all my practice as a trainee teacher. In this way, this Internship Report will act as a register of my journey, of the lived and written experiences in the first person to witness what was most significant to me. My actions, difficulties as well as my learning experience that led to my growth in the transition from a student to a trainee teacher will be revealed in this report. I will describe my course and the responsibility of teaching two groups of the 11th grade and a 5th grade class as well. Several different stages had to be overcome, based on reflection on the difficulties, doubts, solutions and learnings.This document is organized in the following way: (1) Introduction - contextualization and a brief clarification of what is stated in this report; (2) Biographical Framework - which characterizes me and my course, (3) Professional practice framework - presentation of the real context experienced during the professional internship and all agents involved; (4) Realization of professional practice- reflection on my pedagogical practice as a trainee teacher; (5) Professional Development- (6) Final considerations about the internship year. In this context, especially in chapter five, it was also possible to investigate a problem felt by Physical Education teachers at Rocha Peixoto Secondary School, which justified the pertinence of a study focused on the perception of students' opinions about the curriculum of the discipline of PE. and prospects for the future.The acquired learnings allowed to truly know the meaning of the profession as a teacher and the learning process.